2018
DOI: 10.1186/s12955-018-0976-x
|View full text |Cite
|
Sign up to set email alerts
|

The validation of the Short Warwick-Edinburgh Mental Well-Being Scale (SWEMWBS) with Deaf British Sign Language users in the UK

Abstract: BackgroundThere is no validated measure of positive mental well-being that is suitable for Deaf people who use a signed language such as British Sign Language (BSL). This impedes inclusion of this population in a range of research designed to evaluate effectiveness of interventions. The study aims were: (i) to translate the original English version of SWEMWBS into BSL and to test the SWEMWBS BSL with the Deaf population in the UK who use BSL; (ii) to examine its psychometric properties; and (iii) to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
(37 reference statements)
0
26
0
1
Order By: Relevance
“…This item was not included in the 7-item short WEMWBS (SWEMWBS), and the latter is more preferable for monitoring mental well-being in large-scale population studies given its robust measurement properties and brevity [13,14]. The SWEMWBS has been validated in deaf British sign language users [15], Norwegian and Swedish adults [16], Norwegian adolescents [17], people with schizophrenia, depression and anxiety spectrum disorders in Singapore [18], and hospitalized patients with mental illness in Hong Kong [19]. The SWEMWBS was developed to support mental health promotion programs and has the advantage of a low ceiling effect in population samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This item was not included in the 7-item short WEMWBS (SWEMWBS), and the latter is more preferable for monitoring mental well-being in large-scale population studies given its robust measurement properties and brevity [13,14]. The SWEMWBS has been validated in deaf British sign language users [15], Norwegian and Swedish adults [16], Norwegian adolescents [17], people with schizophrenia, depression and anxiety spectrum disorders in Singapore [18], and hospitalized patients with mental illness in Hong Kong [19]. The SWEMWBS was developed to support mental health promotion programs and has the advantage of a low ceiling effect in population samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, the validity and reliability of the SWEMWBS in the general population of Hong Kong is unknown. Previous studies have identified that the SWEMWBS items can be loaded on one factor using a principal component analysis [15][16][17]19] and confirmatory factor analysis [16][17][18]. A confirmatory factor analysis is typically used in scale development [20], but it has yet to be conducted for the Chinese version of the SWEMWBS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the good psychometric properties of the WEMWBS, recent literature has indicated some problems related to the items' hierarchy and the existence of gender-biased questions [27]. In response, a shortened version of the WEMWBS (called the SWEMWBS) has been proposed and validated [20,26,[28][29][30][31]. Fung [32] has demonstrated that the SWEMWBS possesses better construct validity than the full version of the WEM-WBS and thus the purpose of our next study will be to create a Polish version of the SWEWBS.…”
Section: Introductionmentioning
confidence: 99%
“…Aanondsen et al, 2019;Andrade et al, 2019;Berke et al, 2019;Chaveiro et al, 2013;Jones et al, 2006;Montoya et al, 2004;Moore et al, 2013;Pardo-Guijarro et al, 2013;Roberts et al, 2015; Rogers et al, 2013a Rogers et al, , 2013bRogers et al, , 2014Samady et al, 2008. 3 Berman et al, 2000Brauer, 1993;Cornes et al, 2006;Cornes and Brown, 2012;Crowe, 2002; Fellinger et al, 2005; Glickman and Carey, 1993; Graybill et al, 2010;Levinger and Ronen, 2008;Rogers et al, 2016Rogers et al, , 2018Smith and Samar, 2016;Tweney and Hoemann, 1973; Wahlqvist et al, 2016. 4 For challenges and facilitators to translation/adaptation,Rogers et al (2018) signposts readers toRogers et al (2013b).…”
mentioning
confidence: 99%
“…3 Berman et al, 2000Brauer, 1993;Cornes et al, 2006;Cornes and Brown, 2012;Crowe, 2002; Fellinger et al, 2005; Glickman and Carey, 1993; Graybill et al, 2010;Levinger and Ronen, 2008;Rogers et al, 2016Rogers et al, , 2018Smith and Samar, 2016;Tweney and Hoemann, 1973; Wahlqvist et al, 2016. 4 For challenges and facilitators to translation/adaptation,Rogers et al (2018) signposts readers toRogers et al (2013b).…”
mentioning
confidence: 99%